The relationship between employee commitment and employee performance among support staff at Lembaga Hasil Dalam Negeri (LHDN) Kuching, Sarawak/ Siti Nurhaida Kamaluddin - Kamaluddin, Siti Nurhaida (2018)
The aim of the study is to examine the relationship between employee commitment and employee performance among the staff. This study utilized a sample consists of 100 support staffs in Lembaga Hasil Dalam Negeri (LHDN), Kuching Sarawak. This study was accomplished through quantitative method for data collection which is questionnaire. Pearson Correlation Coefficient analysis were also carried out for collecting the data. The correlation revealed that continuance commitment is the highest variable among affective commitment and normative commitment with moderate correlation which is positive direction, significance and strong relationship (r=.362, p<0.01) towards job performance. It can conclude that staffs at Lembaga Hasil Dalam Negeri (LHDN) were motivated to stay only because for them leaving would be costly. It means that these variable correlated with each other. Meanwhile, normative commitment also indicates the relationship with job performance with positive direction, relationship and significance (r=.323 ,p<0.01). This finding indicated that it is recommends for future studies to further investigate the different types of employees commitment are used in the organization. Thus, management can incorporate these findings to assist employees to improve their commitment in such a way to enhance the employees’ job performance.